Homophonic Pun in “Alice in Wonderland” in English and Armenian - Matevosyan, Armine; Alimyan, Marine (Armenian Folia Anglistika, 2014)
The article focuses on the theoretical and practical issues of the homophonic pun in “Alice in Wonderland” and its Armenian translation. A pun is a rhetorical device in which people use the polysemous or homonymous relation of a language to cause a word, a sentence of a discourse to involve two meanings. The research reveals that L. Carroll uses a great array of homophonic pun which reveals the quintessential feature of the work, i.e. humor.